Akulturasi Budaya Pada Tradisi Buang-Buang di Desa Tempapan Kuala Kabupaten Sambas, Kalimantan Barat - Etriadi (Jurnal Ilmu Sosial dan Humaniora, 2023)
The area of West Kalimantan, Sambas Regency, still carries out ancestral rituals that have been acculturated to Islamic culture, namely the ritual of wasting. The purpose of this research is to find out the acculturation process of Islam and local culture in the wasting tradition in the people of Tempapan Kuala Village and to find out the forms of acculturation of Islam in the wasting tradition. The methods used in this study are as follows; Heuristics, Verification, Interpretation and Historiography. The results of the research show that: The Wasting Tradition aims to keep people away from the dangers sent down by God for the sins that have been committed by humans. The dangers are in the form of prolonged heat, failure of agricultural businesses, and the spread of disease outbreaks. The form of Islamic acculturation in the local culture in the tradition of wasting is in the form of Sirih kapur, at least three sheets with the same fins, complete with gambier or some peeled betel nuts, gental cigarettes, namely nipa leaf cigarettes with a charm and spells. Frankincense and incense (censer). Pendupa means a place for incense in the form of a flat made of pottery or copper with coals made of wood. Yellow sticky rice with one raw chicken egg served in a flat white glass plate. A knife or a piece of iron or a nail, as hardener.